Modern Trends of Development and Assessment of Professional Potential of the Teaching Staff Abroad - V. Yankovskaya, Veronika; N. Babkina, Lyudmila; N. Kukushkin, Sergey; Yu. Ladogina, Anastasiya; A. Kemkhashvili, Teimuraz (International Journal of Engineering and Technology, 2018)
The relevance of the problem is determined by the increasing requirements for graduates as potential employees.Â The aim of the paper is to investigate the requirements for the product of the system as a whole and for the leading element of this system, in particular [14]. The paper discusses the results of studying the parameters of the complex phenomenon "The problems of the formation of new content and the results of the work of the faculty". To achieve this goal, the following tasks were accomplished:- the factors and causes that trigger a change in higher education and faculty were identified;- a comparative assessment of the criteria of the working conditions of various concepts and their impact on the work of employees in higher education was carried out;- main stages of the professional capacity development process and the sequence of their implementation were determined.The leading scientific approach to investigating this problem was the institutional approach.The main results of the paper are as follows:1. The main stages and sequence of the process of professional potential development were identified;2. The approach of improving the qualification of the teaching staff was suggested;3. The model of adaptation and professional orientation of the teacher was defined.The materials of this paper may be useful for the practical activities of the education system.